Essential Oil Composition of Two Sideritis L. Taxa from Turkey: A Chemotaxonomic Approach - Kilic, Omer (Asian Journal of Chemistry, 2014)
In this study two Sideritis L. taxa from Turkey (Sideritis montana L. subsp. montana and Sideritis vulcanica Hub.-Mor.) have been studied to determine taxonomical classification based on chemical characters. For this purpose hydro distilled essential oil aerial parts of Sideritis montana subsp. montana and Sideritis vulcacina were investigated by GC and GC-MS, forty and forty three compounds were identified representing 90.1 and 92.1 % of the oil, respectively. The yield of oils are about 0.30 and 0.40 mL/100 g, respectively. b-Caryophyllene (30.3 %), a-pinene (12.7 %) and b-pinene (10.6 %) in S. montana subsp. montana, a-pinene (15.5 %), b-caryophyllene (13.2 %) and 1,8-cineole (9.9 %) were identified as main components in S. vulcacina. The chemical distribution of the essential oil compounds in the genus pattern were discussed in means of chemotaxonomy and natural products.